PEMBELAJARAN PERUBAHAN ENERGI MELALUI MEDIA PEMBELAJARAN PREZI PADA SISWA KELAS III SD NEGERI 001 MERDEKA BANDUNG - Pribadi Akhdiat Putra; Uus Kuswendi (IKIP Siliwangi, 2021)
This research aims to (1) identify the use of Prezi learning media as a teacher's aid during teaching and learning activities (2) to analyze the responses of teachers and students during teaching and learning activities through Prezi learning media; (3) Analyze the difficulties experienced by teachers and students during teaching and learning activities through Prezi learning media. The research method used is a qualitative descriptive method with the lecture method. Participants in this study were teachers and students. The instruments used in this study used interview, observation and documentation instruments. The stages of data analysis in this study were (1) lesson planning using Prezi learning media; (2) making Prezi learning media; (3) the use of prezi learning media when teaching and learning activities take place. The results show that the prezi learning media is very helpful for teachers in explaining the subject matter of energy changes, student learning motivation through prezi learning media has increased compared to learning using conventional methods. The difficulties experienced by the teacher, namely; 1) the process of making Prezi media takes a long time 2) the teacher's ability to operate the software as well as the internet; 3) The use of prezi media depends on the creativity of each teacher. As for the difficulties faced by students, the prezi display did not attract the attention of students, so that students began to get bored in the middle of teaching and learning activities taking place.